A Gondwanan perspective on the Ordovician Radiation constrains its temporal duration and suggests first wave of speciation, fuelled by Cambrian clades. (16th September 2017) - Colmenar, Jorge; Rasmussen, Christian M. Ø.
Abstract : This study presents a Cambrian–Ordovician (Cambrian, 'Series 3' – Katian, Ka4) brachiopod α‐diversity curve for the Iberian terrane. Three diversity pulses characterized the northern Gondwanan margin through the studied interval; an initial increase in linguliformean diversity that culminated during the Tremadocian (Tr3); a second, Darriwilian (Dw2) pulse caused primarily by a rise in orthid species; and a third pulse during Katian times (Ka3–4) marking the most diverse and phylogenetically complex faunas recorded in this study. Each of the three diversity pulses is phylogenetically distinct and characterized by large turnover rates. The first pulse consists almost exclusively of remnants of the Cambrian Evolutionary Fauna, whereas the second pulse shows a sudden rise of clades typical of the Paleozoic Evolutionary Fauna. The fact that otherwise typical Cambrian clades also radiated at the dawn of the Ordovician suggests that whatever facilitated the emerging Ordovician Radiation, also benefitted these ancient lineages. However, eventually the succeeding Paleozoic Evolutionary Fauna came to dominate during the second diversity pulse. This pulse represents a high‐latitude correlative to the main pulse of the Ordovician Radiation. Although it coincides with a globally occurring transgression of eustatic nature, our analysis shows that the generic composition remained overwhelmingly endemic up through the Darriwilian–Sandbian interval. Opposed to this, the third pulse coincides with the globally occurring Boda warming event, which also marks a time of global dispersal. In Iberia, this is reflected by almost entirely cosmopolitan brachiopod faunas, suggesting that the phases of rapid speciation which characterize the Ordovician Radiation had ceased by the mid‐Katian.